2013
DOI: 10.1111/tbj.12180
|View full text |Cite
|
Sign up to set email alerts
|

Benign Papillomas Diagnosed on Large-gauge Vacuum-Assisted Core Needle Biopsy which Span <1.5 cm Do Not Need Surgical Excision

Abstract: The objective of our study is to determine if a carefully selected subset of benign breast papillomas (size ≤1.5 cm) can be safely followed by imaging surveillance instead of immediate surgical excision. Over a 6½-year period, 86 breast lesions were diagnosed as a benign papilloma (BP) utilizing an 11- or 8-gauge vacuum-assisted core needle biopsy (VACNB) device. In general, it was our intent to remove as much of the radiologically evident lesion as possible. These 86 lesions underwent ≥2 years of imaging surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
0
23
1
1
Order By: Relevance
“…Only one study by Chang et al evaluated the accuracy of VAB in PL without atypia by open surgical excision following VAB with no upgrade to malignancy but an upgrade of 18.3 % to atypia [61]. Most studies following up VAB excision of PL without atypia did not observe any upgrade to malignancy with at least 2 years of surveillance [60, 62, 63]. One recorded a minimal underestimation of 1.4 % [64] and another 3.2 % [65].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study by Chang et al evaluated the accuracy of VAB in PL without atypia by open surgical excision following VAB with no upgrade to malignancy but an upgrade of 18.3 % to atypia [61]. Most studies following up VAB excision of PL without atypia did not observe any upgrade to malignancy with at least 2 years of surveillance [60, 62, 63]. One recorded a minimal underestimation of 1.4 % [64] and another 3.2 % [65].…”
Section: Resultsmentioning
confidence: 99%
“…One reason might be the fact that the size of the PL was not recorded, implying that some PL might not have been completely removed. Mosier et al removed only lesions smaller than 15 mm (range 3–15 mm) to ensure the complete removal of the PL [62]. With this approach, they had no upgrades to malignancy after nearly 9 years.…”
Section: Resultsmentioning
confidence: 99%
“…The upgrade rate was higher when using CNB than using VAB (p = 0.021). Many studies [2, 11,12] have suggested that a wider biopsy might lead to lower upgrade rate. This seemed to suggest that imaging surveillance might be suitable for small papillomas undergoing VAB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these earlier studies had several imitations, including relatively small study sizes or unconfirmed pathological results from surgery for many cases. Future research with larger studies and sufficient surgical outcomes will be necessary to address these limitations [14151617202324]. …”
Section: Discussionmentioning
confidence: 99%